Essays on Monetary Policy Impacts on Wage Inequality - Amegble, Koami Dzigbodi (Université d'Ottawa / University of Ottawa, 2025)
Chapter 1 - This paper examines the impact of non-systematic monetary policy on wage inequality in Canada, using two key measures: the wage Gini index, which captures overall wage dispersion, and the wage ratio, which reflects disparities between high- and low-skilled workers. We obtain a non-systematic monetary policy innovations measure from an estimated standard Taylor rule. To estimate cumulative impulse response functions over the short and medium terms, we employ a smooth local projection method. Controlling for lagged oil price returns, employment rate, and fiscal policy variables, we find no significant effects on the wage Gini coefficient. On the other hand, contractionary monetary policy shocks widen the skill-based wage gap (over the two-year horizon), and expansionary monetary policy shocks narrow it (over both the one- and two-year horizons). These findings highlight the nuanced role of monetary policy in shaping wage dynamics and equitable labour market outcomes. Chapter 2 - This paper proposes a novel approach for comparing impulse response functions across groups of countries, regions, or monetary zones. Our test statistics are Wald-type statistics with a weighting matrix that accounts for cross-sectional dependency. Instead of using HAC correction for the time dependency, we propose a non-overlapping block bootstrap procedure for the test. We assess the properties of the test by simulation. Our main findings are: (1) our proposed test has good size and power properties in finite samples; (2) the χ² approximation does not suffice to control size; and (3) the test performs well for assessing short-, medium-, and long-term impacts, both non-cumulative and cumulative impacts. Chapter 3 - This paper examines the heterogeneous effects of non-systematic monetary policy on wage inequality across Canadian provinces. Using two measures of wage inequality - the Gini coefficient and the wage ratio between high- and low-skilled workers - and a monetary policy innovation series derived from a Taylor rule framework, our smooth local projection based analysis reveals that the effects of non-systematic monetary policy on wage inequality vary significantly across regions. In particular, regional heterogeneity is more pronounced when we consider the entire wage distribution. Moreover, these effects are asymmetric: expansionary monetary policy shocks lead to more heterogeneous regional responses in wage inequality than contractionary monetary policy shocks.
Keywords: Non-Systematic Monetary Policy; Smooth Local Projection; Heterogeneity Test; Non Overlapping Bloc Bootstrap; Residualized shock; Impulse Response Functions; Power; Size; Wage Inequality